Застосування Есенціалє Форте Н для корекції порушень гомеостазу у вагітних з прееклампсією - Резніченко, Галина Іванівна; Резніченко, Юрій Григорович; Головко, Г. В.; Потебня, В. Ю.; Резниченко, Г. И.; Резниченко, Ю. Г.; Reznichenko, G. I.; Reznichenko, Yu. G.; Golovko, G. V.; Potebnya, V. Yu. (My University, 2008)
Вивчена ефективність застосування препарату Есенціалє Форте Н у вагітних з прееклампсією. Встановлено, що в пацієнток з прееклампсією є прояви ендотоксикозу, активація ферментної ланки гомеостазу, порушення обміну фосфоліпідів. Застосування Есенціалє Форте Н дозволяє ефективно нормалізувати зазначені показники, попередити розвиток тяжких ускладнень прееклампсії, зменшити частоту ускладнень у пологах та знизити захворюваність новонароджених. Це дає підставу рекомендувати до широкого застосування Есенціалє Форте Н у вагітних з прееклампсією. Изучена эффективность применения препарата Эссенциале Форте Н у беременных с преэклампсией. Установлено, что у пациенток с преэклампсией имеются проявления эндотоксикоза, активация ферментной цепи гомеостаза, нарушения обмена фосфолипидов. Применение Эссенциале Форте Н позволяет эффективно нормализовать указанные показатели, предупредить развитие тяжелых осложнений преэклампсии, уменьшить частоту осложнений в родах и снизить заболеваемость новорожденных. Это дает основания рекомендовать к широкому применению Эссенциале Форте Н у беременных с преэклампсией. The effectiveness of the use of the preparation Essentiale Forte N in pregnant women with preeclampsia has been studied. It has been fixed that there are manifestations of endotoxicosis, making active of enzyme unit, violations of phospholipids metabolism in patients with preeclampsia. The use of Essentiale Forte N permits to normalize effecH tively the appointed indexes, to prevent the development of severe complications of preeclampsia, to decrease the quantity of delivery complications and to decrease the sickness rate in newborns. This gives the reason to recommend the wide use of Essentiale Forte N in pregnant women with preeclampsia.
Применение Эссенциале Форте Н для коррекции нарушений гомеостаза у беременных с преэклампсией
The use of Essentiale Forte N for homeostasis violations correction in pregnant women with preeclampsia
Keywords: прееклампсія; лікування; Есенціалє Форте Н; преэклампсия; лечение; Эссенциале Форте Н; preeclampsia; treatment; Essentiale Forte N